Usefulness of combined CARTO electroanatomical mapping and manifest entrainment in ablating adenosine triphosphate-sensitive atrial tachycardia originating from the atrioventricular node vicinity - Ken Okumura, M.D. (Journal of Arrhythmia, 2016)
Background: By using a noncontact mapping system, adenosine triphosphate (ATP)-sensitive atrial tachycardia (ATP-AT) originating from the atrioventricular (AV) node vicinity was successfully ablated at the entrance to the slow conduction zone indicated by the manifest entrainment technique. We aimed to prospectively validate the efficacy of the combination of CARTO electroanatomical mapping and manifest entrainment in ablating this ATP-AT. Methods: Of the 27 AT patients from January 2013 to March 2014, 6 patients with sustained ATP-AT were studied (age, 67±13 years; tachycardia cycle length, 350±95 ms). We first created the CARTO map during AT, and performed rapid pacing from the anterior right atrial wall (ARAW) and cavotricuspid isthmus (CTI) approximately 30 mm remote from the earliest activation site (EAS). We identified the site where manifest entrainment, defined as the orthodromic capture of the EAS with a long conduction time, was observed, and ablated the site approximately 20 mm remote from the EAS, between the pacing site and the EAS. Results: Manifest entrainment was demonstrated in all patients paced from the ARAW (four patients) and from the CTI (two patients). Ablation at the prespecified site terminated AT in 6±3 s, and AT became no longer inducible in all patients. At the successful ablation sites, discrete atrial electrograms were recorded; however, low-amplitude, fractionated electrograms suggestive of slow conduction were not observed in all patients. The atrio-His interval during sinus rhythm remained unchanged (from 96±12 to 89±7 ms, p=NS). During 11±6 months, no patients showed AT recurrence and AV conduction abnormality. Conclusion: CARTO mapping- and manifest entrainment-guided ablation strategy is effective and safe in the treatment of ATP-AT.